Filament Engineering of Two‐Dimensional h‐BN for a Self‐Power Mechano‐Nociceptor System (Small 16/2022). Issue 16 (21st April 2022) - Ding, Guanglong; Chen, Ruo‐Si; Xie, Peng; Yang, Baidong; Shang, Gang; Liu, Yang; Gao, Lili; Mo, Wen‐Ai; Zhou, Kui; Han, Su‐Ting; Zhou, Ye
Abstract : Mechano‐Nociceptor Systems In article number 2200185, Ye Zhou and co‐workers develop a diffusive memristor with better behaviors of conductive filaments and higher device uniformity based on 2D h ‐BN, which could be used as an artificial nociceptor to mimic biological nociceptor properties. Moreover, a self‐powered mechano‐nociceptor is demonstrated by connecting a self‐made triboelectric nanogenerator with the memristor.